2022
DOI: 10.3390/electronics11071043
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Cardioid Slot Antenna for Super Wideband Applications

Abstract: A new geometry for uniplanar, ultra-wideband monopole antenna has been proposed for operations in the 1.8–30 GHz band, thanks to its fractal structure in the form of a cardioid. The antenna has extremely small dimensions at 0.21λ × 0.285λ at the lowest frequency of 1.8 GHz. A parametric analysis of the influence of certain antenna dimensions on its characteristics was performed in order to achieve the widest possible impedance bandwidth. This antenna is designed for low-cost FR-4 substrate because it is primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Jellemz ően egysávos antenna, amelyet leggyakrabban a földi kommunikációban használnak [5]. A kardioid formát tartalmazó fraktálok használata az antennákban lehet ővé teszi az összes kereskedelmi frekvenciasáv lefedését az 1,8-30 GHz-es frekvenciatartományban, miközben az antenna kis mérete megmarad a fraktálok térkitölt ő képességének köszönhet ően, ezért a fraktál antenna felhasználható az energiabegy űjt ő rendszerekben, valamint a IoT, WLAN, mobil MIMO és m űholdas kommunikációs rendszerekben és radarokban is [6]. Parallel módon a kardioid a hangtechnikában is jelent ős szereppel bír.…”
Section: Bevezetésunclassified
“…Jellemz ően egysávos antenna, amelyet leggyakrabban a földi kommunikációban használnak [5]. A kardioid formát tartalmazó fraktálok használata az antennákban lehet ővé teszi az összes kereskedelmi frekvenciasáv lefedését az 1,8-30 GHz-es frekvenciatartományban, miközben az antenna kis mérete megmarad a fraktálok térkitölt ő képességének köszönhet ően, ezért a fraktál antenna felhasználható az energiabegy űjt ő rendszerekben, valamint a IoT, WLAN, mobil MIMO és m űholdas kommunikációs rendszerekben és radarokban is [6]. Parallel módon a kardioid a hangtechnikában is jelent ős szereppel bír.…”
Section: Bevezetésunclassified
“…Results confirmed that the proposed antenna is miniaturized by 4.30% compared to the smallest prototype and provides a wider operating bandwidth than other designs. The proposed design also offers better RBW and FBW than [7][8][9][10][11][16][17][18] with higher BDR [15]. Furthermore, the proposed design offers a high peak gain compared to the designs listed in Table 2.…”
Section: Fabrication and Validationmentioning
confidence: 99%
“…Through a combination of a flower-shaped radiator and an elliptical ground plane, a bandwidth of 3.7 to more than 60 GHz was achieved with an FBW of greater than 176.76% and a BDR of 2780.108. In [18], a slot antenna was presented for SWB applications. The IBW in the frequency range of 1.8-30 GHz was achieved by using a cardioid-like radiating structure and a slot.…”
Section: Introductionmentioning
confidence: 99%
“…A 50 ohm impedance feed line is perfectly matched with a corner twisted-type rectangular radiating structure on the upper side and to the defective ground surface. The designed antenna has triple broad notch band characteristics between the WLAN band at 4-6 GHz, the satellite communication band at 7.6-9.8 GHz, and the 10.5-11.5 GHz band [15]. A unique heart symbol-shaped electrically compact antenna attached to a planar AMC-artificial magnetic conductor on an FSS-frequency selection surface for use in WLAN (i.e., 5.8 GHz) and WiMAX (i.e., 3.5 GHz) applications is designed in [16].…”
Section: Introductionmentioning
confidence: 99%